Baseline Cardiopulmonary Resuscitation Skill Performance of Nursing Students Is Improved After One Resuscitation Quality Improvement Skill Refresher. Issue 2 (March 2020) - Kardong-Edgren, Suzan; Oermann, Marilyn H.; Jastrzembski, Tiffany S.; Krusmark, Michael A.; Gluck, Kevin A.; Molloy, Margory A.; Miller, Carrie Westmoreland; Webb, Suzanne; Frost, Erica; Sarasnick, Janice A.
Abstract : This article reports the results of baseline cardiopulmonary resuscitation (CPR) skills performance measurements from 467 nursing students. All participants had completed a CPR course. Baseline measurements were compared to performance after one 10-minute refresher training session on the Resuscitation Quality Improvement system. Significant improvements were made after the computer- and practice-based refresher. Findings suggest that staff developers should evaluate the use of audio and visual feedback devices to improve the quality of CPR provided by clinical staff.